Job satisfaction and psychological factors influence the caring behavior in nurses in Sierra Leone: a cross-sectional study - Wang, Xiao; Xue, Juan; Zhang, Aidi; Luo, Yaoyue; Chen, Ouying; Liu, Caixia; Zhang, Jie; Wu, Meirong (Frontiers in Psychology, 2024)
Objective Identifying the status of caring behavior and its influencing factors in nurses is crucial for improving the quality of care for patients. However, there is a lack of studies on this in Sierra Leone. This study explored the status of caring behavior and associated factors in nurses working in Sierra Leone. Study design A cross-sectional descriptive survey was conducted from October 3 to December 15, 2022, with clinical nurses recruited through convenience sampling. Methods The participants included 360 nurses from various nursing departments from 12 hospitals in Sierra Leone. Measurements included a general information questionnaire, the Caring Behavior Inventory, Connor-Davidson Resilience Scale, McCloskey/Mueller Satisfaction Scale and Zung’s Self-Rating Anxiety Scale. Descriptive statistics, one-way analysis of variance and independent-sample t-tests, Pearson’s correlation analyses, and multiple regression analyses were performed. Results Caring behavior score was 128.97 (SD 11.967); it significantly and positively correlated with job satisfaction and resilience and negatively correlated with anxiety. Linear regression analysis showed that resilience, job satisfaction, anxiety, daily working time, and position were the main predictors of caring behavior. Conclusion The level of caring behavior in nurses in Sierra Leone was moderate. Resilience and job satisfaction significantly and positively predicted nurses’ caring behavior. Anxiety, daily working time, and position are important factors of caring behaviors. Implications for practice It is suggested to create a conducive working environment, reduce the excessive workload of nurses, enhance their positive psychological state, and their job satisfaction by providing recognition and rewards to improve the level of nurses’ caring behavior.